The many interactions between the innate immune system and the response to radiation. Issue 2 (28th November 2015) - Candéias, Serge M.; Testard, Isabelle
Highlights: Inflammation can protect against radiation toxicity. Nucleic acids are sensed as danger signals to activate the innate immune system. Radiation exposure induces the expression of pro-inflammatory genes by mechanisms depending on ATM, p53 and NF-kB. Abstract: The role of the immune system in the protection of the organism against biological aggressions is long established and well-studied. A new role emerged more recently in the protection from – and the response to – physical trauma such as exposure to ionizing radiation. A pre-existing inflammation, induced by administration of an inflammatory cytokine or of a Toll-like receptor agonist, is indeed able to mitigate the toxic effects of acute radiation exposure. Conversely, it appears that the innate immune system can be activated during the course of the cellular response to radiation. Activation of different sensors and pattern recognition receptors by intra-cellular molecules such as HMGB1 or DNA released in the extra-cellular milieu or in the cytosol by irradiated cells induces the production of inflammatory and anti-viral cytokines. In addition, in human monocytes and macrophages, the expression of inflammatory cytokine genes can be directly induced by p53- and ATM-dependent mechanisms. This last finding establishes a direct link between radiation-induced DNA damage response and radiation-induced inflammation.